In Vitro Propagation of Croton Scabiosus Bedd. (Euphorbiaceae), an Endemic and Vulnerable Tree Species - Prasad Rao, B. Ravi; Salamma, S. (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Croton scabiosus Bedd. (Euphorbiaceae), an endemic tree species of Southern Eastern Ghats of Andhra Pradesh, India, categorised as ulnerable is attempted for in vitro propagation. Seed pathological problems, poor germination, recurrent fires and tree fellings in the native habitat are the major threats of the species. With an objective to standardise a suitable multiplication protocol to augment the species population in the natural habitat, the present study focus on multiplication of the species through micropropagation. Of the various growth regulators employed in the experimentation, maximum mean number of shoots i.e. 5.37±0.12 was found on MS medium fortified with 0.5mg/l BAP and 2.5mg/l IAA. Maximum mean length of shoots 5.2±0.14 was found on 0.5mg/l BAP+1mg/l IAA. In vitro rooting was found on half strength MS medium fortified with 2.5mg/l IBA (8.92±0.19 mean number of roots with 5.04±0.05 mean length of roots with 90% response). Only 10% of survival rate was observed and the species warrants effective on site conservation methods.